2018
DOI: 10.1002/jat.3737
|View full text |Cite
|
Sign up to set email alerts
|

Type of endothelial cells affects HepaRG cell acetaminophen metabolism in both 2D and 3D porous scaffold cultures

Abstract: Recent advances in developing in vitro tissue models show that function of hepatocytes is altered in when cultured in 3D configuration and co‐culturing with various non‐parenchymal cells. However, tissue source for such non‐parenchymal cells on viability and metabolic products of hepatocytes have not been explored. In this study, we evaluated the effect of 2D and 3D cultures either with HepaRG cells alone or in combination with liver sinusoidal endothelial cells (LSECs) and human umbilical vein ECs (HUVECs). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…93 A chitosan-gelatin porous structure with a pore size of 84-150 mm has been a suitable environment for cell infiltration. 92 Another method for increasing the porosity, which in combination with other methods such as the microsyringe technique can provide smaller pores (10-30 mm), is particulate leaching with different particles such as glucose grains, which can be washed with deionized water. 109 Therefore, tailoring the pore size and porosity is an essential consideration in manufacturing scaffolds.…”
Section: Extracellular Matrixmentioning
confidence: 99%
See 2 more Smart Citations
“…93 A chitosan-gelatin porous structure with a pore size of 84-150 mm has been a suitable environment for cell infiltration. 92 Another method for increasing the porosity, which in combination with other methods such as the microsyringe technique can provide smaller pores (10-30 mm), is particulate leaching with different particles such as glucose grains, which can be washed with deionized water. 109 Therefore, tailoring the pore size and porosity is an essential consideration in manufacturing scaffolds.…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…However, these methods had a significant role in the progress of the LTE field. 30,135 There are many methods used for TE approaches, including solvent-casting, [137][138][139][140] freeze-drying, 92,95,138,[141][142][143] electrospinning, [144][145][146][147] phase separation, 103,135 and gas foaming. 77 In this study, we represent some of these techniques that have been utilized in LTE.…”
Section: Extracellular Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…76 On this basis, the researchers optimized the aforementioned scaffold and improved it through laminin incorporation; they found that the cells generated on this scaffold were strikingly similar to a standard hepatocyte cell line in terms of the expression of hepatocyte markers. 77 Moreover, gelatin was also employed to fabricate microcarriers with chitosan for hepatocyte culture, 78 and improved the performance of hepatocytes for as long as 2 months. 79 Chitosan is a linear polysaccharide which has good biocompatibility and wide applications in biomedical fields.…”
Section: Natural Macromoleculesmentioning
confidence: 99%
“…81 Rajendran et al 82 established a chitosan nanofiber scaffold via an electrospinning technique combined with a coculture system that consisted of hepatocytes and fibroblasts, and thus developed a new 3D liver model for the maintenance of long-term liver functions. To obtain better biocompatibility, chitosan can be further modified with other macromolecules, such as collagen, 83 gelatin, 78 alginate, 84 and heparin. 85 For example, Fan et al 86 proved that chitosan/galactosylated hyaluronic acid scaffolds were suitable for improving hepatocytes adhesion and maintaining liver function in a previous work.…”
Section: Natural Macromoleculesmentioning
confidence: 99%